2020
DOI: 10.1108/josm-11-2018-0357
|View full text |Cite
|
Sign up to set email alerts
|

Why customers and peer service providers do not participate in collaborative consumption

Abstract: PurposeTechnological innovations such as smart mobile devices and mobile applications gave rise to a new business model: collaborative consumption. This business model, which is receiving significant attention from researchers and practitioners, is characterized by an intermediating digital platform that facilitates exchanges between customers and peer service providers. However, many digital platform providers still fail to build a critical mass of demand and supply. Accordingly, the aim of this research is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 71 publications
2
42
0
1
Order By: Relevance
“…Access-related barriers for P2P car owners include the perceived risk of limited access to their car (Hazée et al , 2020) and possible damage to the car while rented out. In a study of P2P carsharing in California, Ballús et al (2014) noted that where the platform provider's package did not include insurance, fewer owners were willing to offer their car, as they would incur higher costs in the event of it being damaged.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Access-related barriers for P2P car owners include the perceived risk of limited access to their car (Hazée et al , 2020) and possible damage to the car while rented out. In a study of P2P carsharing in California, Ballús et al (2014) noted that where the platform provider's package did not include insurance, fewer owners were willing to offer their car, as they would incur higher costs in the event of it being damaged.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies on service providers can also contribute to the development of balanced solutions based on better alignment of the service provider and customer requirements. Additionally, the perspective of car owners who rent their cars for P2P carsharing has been neglected by existing research (Haz ee et al, 2020).…”
Section: Key Customer Requirementsmentioning
confidence: 99%
“…Functional and psychological barriers can drive consumer avoidance of engaging with the SE. Barriers include the complexity of digital platforms and the inability of some platforms to build critical mass, the contamination and lack of ownership of shared assets, lack of control over service quality, high competition for idle resources, changes to the legal environment, incompatibility with consumer lifestyles and lack of tangibility of experiential goods (Hazée et al , 2020; Hofmann et al , 2017; Morewedge et al , 2021). Additionally, the building of trust and transparency acts as a major barrier to engagement with the SE, including negative interactions with undesirable consumers, the difficulty of establishing trust and shortcomings of mechanisms for establishing trust.…”
Section: The Sharing Economy (Se)mentioning
confidence: 99%
“…In an effort to facilitate better understanding of why consumers using mobile applications do not engage in collaborative consumption, Hazée et al (2020) employed a qualitative methodology. They found that barriers exist relating to complexity, value, risk, compatibility, contamination, image and responsibility.…”
Section: New Research Contributionsmentioning
confidence: 99%